2012
DOI: 10.4103/0974-620x.99371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myopia and its association with diabetic retinopathy in subjects with type II diabetes mellitus: A population-based study

Abstract: Objective:To report the prevalence of myopia and its association with diabetic retinopathy in subjects with type II diabetes mellitus and compare the diabetic retinopathy status in the myopic group vs the emmetropic group.Design:Population-based study.Materials and Methods:The population-based study estimated the prevalence of myopia from 1058 subjects, who were more than 40 years old and had type II diabetes mellitus; the patients were enrolled from a cross-sectional study. Participants answered a detailed qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… 11 However, date from other epidemiology studies, including Chinese population-based studies, did not find this protective effect of myopia. 2 , 19 21 , 32 , 33 Although the longitudinal results of BES found that the incidence of DR was associated with shorter axial length, the refraction was never found to be associated with prevalence/incidence of DR. 2 , 21 Similarly, Man et al found that the longer axial length rather than myopia was the main contributor for the protective effect. 32 , 33 The inconsistent findings may be due to different definitions or classifications of myopia, methodology of fundus photography and definitions of DR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 However, date from other epidemiology studies, including Chinese population-based studies, did not find this protective effect of myopia. 2 , 19 21 , 32 , 33 Although the longitudinal results of BES found that the incidence of DR was associated with shorter axial length, the refraction was never found to be associated with prevalence/incidence of DR. 2 , 21 Similarly, Man et al found that the longer axial length rather than myopia was the main contributor for the protective effect. 32 , 33 The inconsistent findings may be due to different definitions or classifications of myopia, methodology of fundus photography and definitions of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia was suggested as a protective factor for DR in population-based studies, clinical studies and meta-analysis. 11 18 However, several studies have denied the protective effect for myopia against DR. 2 , 19 21 Regarding the association in Chinese population, data are limited and remain controversial. 2 , 13 , 21 In the Beijing Eye Study (BES) with a moderate sample size (n = 362), Xie et al found that neither the prevalence of DR nor the stage of DR was associated with refractive error.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we suspect that high myopia inhibits the expression of OPN and plays a protective role in DR. However, few studies assert the contrary; Ganesan et al [24] did not find a significant association between high myopia and DR.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although the exact mechanism(s) underlying the protective effect of high myopia against DR is yet to be defined but some studies shows the protective effect of axial length against DR was due to several hypotheses, one hypothesis is that with axial elongation there is narrowing of blood vessels in the retina leading to reduction in retinal blood flow according to Hagen-Poiseuille law resulting in a decrease in capillary hydrostatic pressure and consequent decreased likelihood of leakage and rupture of compromised retinal capillaries in diabetes (Starling and Laplace's law), [28] deformation in the posterior pole, [20] increased ocular volume in an elongated eye, [29] neurodegeneration, neuron dysfunction, [30] thinning of the peripheral retina [30] in axially elongated eyes with resultant decreased metabolic demand then could blunt the hypoxic response which is necessary for diabetic retinopathy, [30] a reduction in vascular endothelial growth factor concentration in the aqueous associated with increasing axial length, [31] an impairment of retinal adaptive circuitry in myopic eyes [32] that might be associated with abnormal reduction of inner retinal function [20] and the development of posterior vitreous detachment [33] that removes the vitreous scaffold for neovascular proliferation and enhances oxygen diffusion across the liquefied vitreous [17] .…”
Section: Discussionmentioning
confidence: 99%